PROCESSIONAL CROSSES IN THE ARMS OF UKRAINIAN AND FOREIGN EPARCHIES: COMPARATIVE ASPECT - Золотарчук, Н. І. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Idea, 2019)
The article analyses the artistic peculiarities of the arms of the clergy of various confessions of Ukrainian and foreign eparchies at the end of the 20th and in the early 21st century, their place (purpose) in the spiritual heritage of this period. Examples of insufficiently studied arms are given, but interesting given the images of processional crosses they have.